1992
DOI: 10.3109/00365519209088371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pivalic acid-containing prodrugs on carnitine homeostasis and on response to fasting in children

Abstract: Treatment of 17 children aged 2-9.5 years with a combination of pivmecillinam and pivampicillin (250-500 mumol 24 h-1) for more than 1 year resulted in a reduction of the free carnitine concentration in serum and muscle to less than 10% of the mean reference value. The decline in serum was slow, with an estimated half-life of about 5 months. Spontaneous replenishment occurred at about the same slow rate. Thus, there is no increase in endogenous carnitine synthesis as a response to increased demand of carnitine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Furthermore, the formation of pivaloylcarnitine following pivampicillin administration has been reported (15,16). Despite the strong attention focused on the effect of pivalic acid on the carnitine level (2,9,10,15,16), there have been no reports about the general disposition of pivalic acid in relation to its safety and toxicity characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the formation of pivaloylcarnitine following pivampicillin administration has been reported (15,16). Despite the strong attention focused on the effect of pivalic acid on the carnitine level (2,9,10,15,16), there have been no reports about the general disposition of pivalic acid in relation to its safety and toxicity characteristics.…”
mentioning
confidence: 99%
“…C]pivaloylglycine and [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]pivaloylcarnitine hydrochloride were synthesized by a reaction of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]pivaloylchloride with glycine and carnitine, respectively, as illustrated in Fig. 2.…”
mentioning
confidence: 99%
“…Holme et al (1992) reported long-term adverse effects of pivalate-containing antibiotics in children, including low muscle carnitine levels. In both of our patients, antibiotics containing pivalate were administered for very long periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in serum carnitine levels has been observed after short-term administration of prodrugs containing pivalate; however, short-term administration is considered safe because the carnitine stored in muscles is believed to be sufficient to maintain the tissue carnitine levels (Brass et al 2003). In contrast, long-term administration of prodrugs containing pivalate can cause hypoketotic hypoglycemia, convulsion, tiredness, behavioral problems and weakness in children (Holme et al 1992;Makino et al 2007).…”
mentioning
confidence: 99%
“…There is little evidence for this postulate. Reported tissue values in these disorders are considerably higher than in the carnitine transport defect or with pivalate administration (2,7,10). One report indicates that the degree of free carnitine deficiency associated with PA and MMA is not severe enough to impair hepatic fatty acid oxidation (28).…”
Section: Panels 1 and 2 Inmentioning
confidence: 99%